The association between healthcare access and shingles vaccination among older adults in Virginia, United States - Chidozie Declan Iwu; Pramita Shrestha; Alyson J. Littman; Julia E. Hood (PLoS ONE, 2025)
Introduction Shingles is a debilitating vaccine preventable disease that poses a health threat to older adults. However, the uptake of shingles vaccines remains low, and the factors contributing to the low uptake are not clearly understood. This study assessed the association between healthcare access and shingles vaccination among older adults, as well as the impact of COVID-19 pandemic on vaccine uptake. Methods This was a cross-sectional study among adults 50 + years in Virginia (n = 16,576) using data from the Behavioral Risk Factor Surveillance System (2018, 2019, and 2021). We calculated the prevalence of shingles vaccination by health insurance and access to primary health care provider (used as proxies for healthcare access) and in relation to the COVID-19 pandemic (pre vs during). Log binomial regression models were used to estimate prevalence ratios (PR), adjusting for confounders. Results Shingles vaccination was substantially higher among those with healthcare access compared to those without. Specifically, shingles vaccination was 35% among those with health insurance vs. 10% among those without (adjusted PR (aPR): 2.03, 95% CI 1.44, 2.86), and 36% among those with a primary healthcare provider vs 15% among those without (aPR: 1.99, 95% CI: 1.65-2.41). Finally, shingles vaccination was 41% during the COVID-19 pandemic vs. 30% before (aPR:1.26, 95% CI: 1.20–1.33). Conclusion Individuals with health insurance and access to a primary healthcare provider were significantly more likely to receive the shingles vaccine compared to those without such access. Moreover, the prevalence of shingles vaccination during the pandemic period was substantially higher compared with shingles vaccination before the pandemic.